Kontrol Jembatan Otomatis Menggunakan Sensor Ultrasonik Berbasis Arduino - Elka Pranita (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2023)
Making controls for unmanned aircraft is an innovation made to make it easier for someone to learn to control an unmanned aircraft. Advances in technology, especially in the field of control systems, make it possible to perform manual tasks automatically. This control design is designed to facilitate the learning process so that the control process can be carried out at any time. Application of methods in designing hardware and software. This tool uses the Arduino Nano microcontroller as the controller and the nrf24l01 sensor for sending and receiving can be done manually or automatically. From the results of the tests carried out, the nrd24l01 sensor can send and receive according to the specified settings. With this tool, it is hoped that beginners can learn to control unmanned aircraft, which originally required quite a high cost to be able to try and learn manually and now can learn at a lower cost and in a short time. Keywords — arduino nano, Remote Control, Nrf24l01